The hybrid operationalization of Brazilian maritime security cooperation in the South Atlantic: an analysis of the West African case between solidarity rhetoric and pragmatic interests - Mercurio, F. (2020)
The main objective of the research is to understand how Brazil operationalized its engagement in maritime security over the South Atlantic Ocean within the framework of the South-South cooperation and how this practice inserted in its Foreign Policy agenda towards West African countries of the Gulf of Guinea, in the period between 2003 and 2014, when the domestic political transformations contributed to positively influence the international participation of the country. More specifically, and through the case study of the multilevel cooperation in maritime security in the Gulf of Guinea, the research theoretically analyses the insertion of this cooperation within the model proposed by the Global South as response to the systemic challenges of the new millennium. The hypothesis that this work is addressing is that the relaunched Brazil's African Policy has been driven by a hybrid posture, an overlapping of both soft power and hard power strategies, also reflected by other emerging powers. They have introduced themselves in many cases as an alternative to the Northern and Western hegemony, affecting the dominant rules and institutions, but that have also adapted themselves to the existing mechanisms and practices. Hence, Brazil has looked at Africa as a stage where to play a protagonist role of leader, by promoting and engaging in bilateral and multilateral forms of cooperation, including the security sector. However, the lacking hard power and material capabilities, as well as the political unwillingness to fully assume the responsibility of its, have made of the international mechanisms of cooperation a Brazilian preferred instrument of power, to be projected over its strategic area. The South Atlantic is today an area highly affected by security threats affecting multiple sectors of global governance and for this reason attracting many external actors. Within these dual features and moved by the desire to relaunch its African policy and guarantee its place in the new reconfiguration of international partnerships with the continent, Brazil is operating within a hybrid theoretical (and empirical) context of solidarity rhetoric about symmetries of power and fair development, on one hand, and a more realist strategy driven by its own interests and projections of power, on the other hand.